- Effect of risk management on settling claims in Sudanese insurance companies - Applied study 2017 - Mohammed, Abdullah Mohammed Abdullah; Mohammed, Sadeq Jadeen Babeker (Journal of Economic, Administrative and Legal Sciences, 2018)
Study  problem is shortage of the payment of claims is directly connected to the risk management mechanism represented in risk selection during the agreement and  insurance price the insurance price is calculated according to scientific ways and it’s not used as a competition factor ,The study aimed at knowing and testing whether the risk management mechanisms in insurance companies works on easy settlement of claims , The study found out that risk agreement scientifically contributes in underwriting quality which leads to easy of claims and putting insurance price through experts and not using it as a competition mechanism enables consistency between the premiums and the claims value
Keywords: risk management; risk management mechanisms; claims settlement